2021
DOI: 10.1038/s41467-020-20317-7
|View full text |Cite
|
Sign up to set email alerts
|

LTD is involved in the formation and maintenance of rat hippocampal CA1 place-cell fields

Abstract: Hippocampal synaptic plasticity includes both long-term potentiation (LTP) and long-term depression (LTD) of synaptic strength, and has been implicated in shaping place field representations that form upon initial exposure to a novel environment. However, direct evidence causally linking either LTP or LTD to place fields remains limited. Here, we show that hippocampal LTD regulates the acute formation and maintenance of place fields using electrophysiology and blocking specifically LTD in freely-moving rats. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…For both groups, the within-day stability was higher than the between-day stability (session 3 vs session 4), suggesting some remapping across days in both groups. This degree of remapping between the first two days in an initially novel environment with a total of 30 min exposure on Day 1 is comparable with that recently reported in WT rats [ 89 ]. However, we cannot exclude the possibility that the lower firing rate map correlations observed between days compared to within days may be due in part to poorer tracking of cells across days than across sessions within a day.…”
Section: Discussionsupporting
confidence: 89%
“…For both groups, the within-day stability was higher than the between-day stability (session 3 vs session 4), suggesting some remapping across days in both groups. This degree of remapping between the first two days in an initially novel environment with a total of 30 min exposure on Day 1 is comparable with that recently reported in WT rats [ 89 ]. However, we cannot exclude the possibility that the lower firing rate map correlations observed between days compared to within days may be due in part to poorer tracking of cells across days than across sessions within a day.…”
Section: Discussionsupporting
confidence: 89%
“…LTD is also essential for memory formation as it counteracts the LTP to allow new memories to form. Recent evidence has shown that LTD may be involved in formation and maintenance of place fields ( 104 ), supporting previous experiments showing that a decrease in the expression of LTD impairs spatial memory retention and consolidation ( 105 , 106 ). It is worth noting that plastic synapses can form positive feedback loops on the rate, temporal, and population coding mechanisms where this positive loop aids the mechanisms in refining and precisely timing the neuronal firing leading to a more efficient information processing.…”
Section: Firing Dynamics Support Plasticitysupporting
confidence: 77%
“…1 h-j), indicating initial enhancement and subsequent reduction in the neural activity. As exploration of a novel environment induces both place cell firing and widespread synaptic depression in the rodent hippocampus [ 9 , 10 ], gradual elevation of hippocampal p-eEF2 level might be associated with synaptic depression and resultant reduced neural activity. In contrast to novel context exploration, acute restraint stress significantly reduced hippocampal p-eEF2 at all (5, 30, and 60 min) timepoints (Fig.…”
Section: Main Textmentioning
confidence: 99%